JAMINAN KEBEBASAN BERAGAMA MENURUT PERSFEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Mustaming, Rohana (Madani Legal Review, 2020)
This writing aims to determine the form of guarantee of religious freedom according to the 1945 constitution of the Republic of Indonesia and Human Rights (HAM) and from the perspective of Isalam law. This research is a qualitative descriptive study using normative, juridical approaches. Secondary data is taken from documents related to research. The data collection technique uses literature study, observation and documentation. The data analysis is done by reducing data, displaying data, verifying data, and providing conclusions. From the results of research and analysis, it is found that, 1) based on articles 28E, 28I, and 29. Limitation on freedom can only be done through the law as stipulated in Article 28J of the 1945 Constitution, (2) protection of religious freedom is guaranteed and protected by constitutional provisions in Indonesia. , law and human rights. Religious freedom has become a joint commitment even though there are two groups of thought, namely religious groups, and nationalist groups (nationalities) giving the opinion that freedom of religion and freedom to practice worship according to their religion and (3) guarantee of religious freedom from the perspective of Islamic law in line with Islamic law Not only provides recognition and guarantees, the Qur'an also obliges Muslims to give religious rights to non-Muslims according to their teachings. It is increasingly clear that Islam has guaranteed and protected freedom of religion and belief.